Sensory Marketing: Comparison of Chinese Restaurants in Indonesia and Hainan (China) on the Satisfaction of Indonesian Tourists - Mbulu, Yustisia Pasfatima; Sahra, Zagita; Reihani, Pradisha; Azzahra, Farisya; Yuntafa, Dziefa Ndaru (E-Journal of Tourism, 2025)
Restaurants are now not only places to eat but also for gathering and business purposes. Product and price are no longer the main factors; restaurants must offer quality service, a comfortable atmosphere, attractive design, and enjoyable experiences to satisfy tourists. This study aims to conduct a comparative analysis and test the sensory marketing dimensions (touch, aroma, taste, hearing, sight) on the satisfaction of Indonesian tourists at the Pantjoran Tea House restaurant in Indonesia and the Guoxiang Siji Farm restaurant in Hainan. Customer satisfaction is measured by five indicators: product quality, price, service quality, emotional factor, and convenience. The method used in this study is a quantitative method with data testing using Partial Least Square (PLS) software, through the SmartPLS program version 3.2.9. The population and sample in this study were customers who visited the Pantjoran Tea House restaurant and the Guoxiang Siji Farm restaurant, with an age range of 17-50 years, and a total of 300 respondents. The results of this study found that the application of sensory marketing at the Pantjoran Tea House restaurant only had one variable that had an influence on the satisfaction of Indonesian tourists, namely the olfactory/aroma dimension, which means that each aroma component is by the expectations of Indonesian tourists in the concept of a Chinese restaurant. Meanwhile, at Guoxiang Siji Farm, sensory marketing in all dimensions affects tourist satisfaction except the auditory dimension